THE FORMATIVE ASSESSMENT BACKWASH IN ENGLISH INSTRUCTION AT KRISTEN NUSANTARA VOCATIONAL SCHOOL - Aji, Kresna Rahma; Hartono, Rudi (English Education Journal, 2019)
This case study focuses on covert backwash of formative assessment in English instruction and aims to provide framework of teacher’s instruction realizations in administering formative assessment.The subject was a teacher selected by certain established categories. Data collection techniques are observational recording, interview, and questionnaire. The instruments of data collection are checklist of lesson plan, interview, observational recording, and questionnaire. The findings consist of twenty claims. The conclusions are (1) teacher’s elicitation as key point, (2) elicitations to develop cognitive, (3) numbers of elicitation depending on the existence of students’ responses, (4) deeper involvement by teacher’s feedbacks, (5) no gap during grammar class orientation, (6) slow response, (7) active and interactive demands for the teacher, and (8) life on-going process of learning. The research suggests English teachers (1) to implement formative assessment conversation (2) to implement the claim because it is helpful in developing student cognition; (4) to provide sometimes of FACC absence for students to get ready into the next step and (5) the non-verbal attributes seen on the teacher facilitated the realization of formative assessment conversation to be understood by the students. This research is only limited on teacher without seeing the backwash on the students’ sides. Since it was sought to see the covert backwash, then the unit of analysis was classroom activity, specifically in formative assessment conversation cycle, in which it was administered orally. Further investigation is expected to see the backwash on other types of formative assessment administration.